Penetrance, pleiotropy, and psychiatry 1 - Vorstman, Jacob A.S. (Henry Stewart Talks, 2021)
Genetic architecture of neurodevelopmental disorders, Common and rare genetic variants, Structural and sequence-level variants, Current genetic testing in pediatric practice, Pleiotropy and variable penetrance, Incidental implications of genetic testing